Sugar and Polymer Excipients Enhance Uptake and Splice-Switching Activity of Peptide-Dendrimer/Lipid/Oligonucleotide Formulations - Saher, Osama (Pharmaceutics, 2019)
Non-viral transfection vectors are commonly used for oligonucleotide (ON) delivery but face many challenges before reaching the desired compartments inside cells. With the support of additional compounds, it might be more feasible for a vector to endure the barriers and achieve efficient delivery. In this report, we screened 18 different excipients and evaluated their effect on the performance of peptide dendrimer/lipid vector to deliver single-stranded, splice-switching ONs under serum conditions. Transfection efficiency was monitored in four different reporter cell lines by measuring splice-switching activity on RNA and protein levels. All reporter cell lines used had a mutated human β-globin intron 2 sequence interrupting the luciferase gene, which led to an aberrant splicing of luciferase pre-mRNA and subsidence of luciferase protein translation. In the HeLa Luc/705 reporter cell line (a cervical cancer cell line), the lead excipients (Polyvinyl derivatives) potentiated the splice-switching activity up to 95-fold, compared to untreated cells with no detected cytotoxicity. Physical characterization revealed that lead excipients decreased the particle size and the zeta potential of the formulations. In vivo biodistribution studies emphasized the influence of formulations as well as the type of excipients on biodistribution profiles of the ON. Subsequently, we suggest that the highlighted impact of tested excipients would potentially assist in formulation development to deliver ON therapeutics in pre-clinical and clinical settings.